TANTANGAN DAN STRATEGI BERWIRAUSAHA KULINER LOKAL, STUDI KASUS LENTOG TANJUNG PAK SISNO KUDUS - Wahyudi, Muhamad; Hadiwinarto, Saputra; Mashuri, Dian Imami; Riesha, Riezky Army (Universitas Islam Negeri Sultan Syarif Kasim Riau Pekanbaru, 2025)
Business dynamics are constantly evolving, and the micro-enterprise sector has significant growth opportunities due to the abundance of entrepreneurs today. Various types of businesses exist within communities, particularly culinary food businesses rooted in local wisdom specific to certain regions. There is substantial potential to enhance micro-economic growth through culinary ventures based on local heritage, such as